Pengaruh Laserpunktur dan Penambahan Probiotik dalam Laju Pertumbuhan Sapi Bali (Bos sondaicus) Jantan - Prakoso, Febriyono Anggela; Adikara, Raden Tatang Santanu; Kusnoto, Kusnoto; Hidanah, Sri; Dhamayanti, Yeni; Warsito, Sunaryo Hadi (Journal of Basic Medical Veterinary, 2020)
The purpose of this study was to determine the effect of laserpuncture shoot towards the growth rate of male Bali cattle. This reasearch was done in July until August 2018 in Cendono Village, Pasuruan. This research uses 18 samples with completely randomized design as a research methods. This research used 18 male Bali cattle aged 2 – 2.5 year. This research divided by 3 groups are the control group (P0, which is without laserpuncture shooting) and two treatment groups (P1, which is laserpuncture shooting with 0.5 joule of doses and P2, which is laserpuncture shooting with 0.5 joule of doses and bioplus probiotic). Laserpuncture shooting already done for 6 weeks with 6 days of interval. The result is weight of cuttle is increasing and it is known from digital weight scales. The data is analyzed by using ANOVA test and followed by Duncan. The result is laserpuncture shooting at the growth point can be increasing the weight of male Bali cattle. Stastical comparison amon P0, P1 and P2 showed there were significant difference on growth rate (p<0.05). The result showed that induction of laserpuncture and bioplus probiotic has effect for growth gain rate of male Bali cattle. The optimal rate of weight gain occured in the second week with laserpuncture induction at dose of 0.5 joule and the six week with laserpuncture induction at dose of 0.5 joule and bioplus probiotic.